2019
DOI: 10.1007/s13577-019-00270-4
|View full text |Cite
|
Sign up to set email alerts
|

mTOR inhibitor everolimus reduces invasiveness of melanoma cells

Abstract: The mammalian target of rapamycin (mTOR) plays a key role in several cellular processes: proliferation, survival, invasion, and angiogenesis, and therefore, controls cell behavior both in health and in disease. Dysregulation of the mTOR signaling is involved in some of the cancer hallmarks, and thus the mTOR pathway is an important target for the development of a new anticancer therapy. The object of this study is recognition of the possible role of mTOR kinase inhibitors-everolimus single and in combination w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Whereas the crucial role of mTOR signaling for cancer cell invasion has been demonstrated in a variety of different tumor cell models, 45 , 46 , 47 , 48 , 49 , 50 the involvement of mTOR in the control of 3D migration of nontransformed cells is not well studied. In an earlier study we found that the invasion potential of primary human fibroblasts depends on mTORC1 and can be induced by hESCs, human induced‐pluripotent stem cells (hiPSCs), and hAFSCs cells via paracrine induction of mTORC1 activity.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas the crucial role of mTOR signaling for cancer cell invasion has been demonstrated in a variety of different tumor cell models, 45 , 46 , 47 , 48 , 49 , 50 the involvement of mTOR in the control of 3D migration of nontransformed cells is not well studied. In an earlier study we found that the invasion potential of primary human fibroblasts depends on mTORC1 and can be induced by hESCs, human induced‐pluripotent stem cells (hiPSCs), and hAFSCs cells via paracrine induction of mTORC1 activity.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, AKT1 activation is sufficient to transform noninvasive melanoma into an invasive form in vivo [80,160]. Downstream effectors of AKT1, such as the mTORC1 protein, have key effects on the metabolism of melanoma cells [5,55,161].…”
Section: Pten and Akt1-regulating Both Glycolysis And Oxidative Phosphorylationmentioning
confidence: 99%
“…Because of the importance of the PI3K/AKT1 signaling axis in cancer proliferation and metabolism, treatments targeting the pathway could be promising. Everolimus, a treatment that inhibits both mTORC1 and mTORC2, has been shown to reduce the invasiveness of melanoma cells [161]. A phase I clinical trial combining the BRAF inhibitor vemurafenib and everolimus showed generally favorable results for patients with advanced cancers, along with no excessive toxicity [170].…”
Section: Pten and Akt1-regulating Both Glycolysis And Oxidative Phosphorylationmentioning
confidence: 99%
“…Therefore, although CR and rapamycin both function to extend health and lifespan consistently across organisms, the impacts of these compounds are transcriptomically varied. Human melanoma cells: Lu1205, WM793 (5 nm, 24 h) [221] ↓ 3xTg-AD mice (AD model) (One dose of 0.167 µg/µL in a volume of 6 µL) [222] ↓…”
Section: Rapamycinmentioning
confidence: 99%
“…In some human cancers, this exerts an antiproliferative effect, inhibiting migration and angiogenesis [230], parallel to CR, AAR, and rapamycin [230]. Everolimus alone, or combined with other anticancer agents, has been shown to attenuate cancer cell growth, promote increased cell death, and increase patient survival [221,224,225,231,232]. Sabine et al [233] observed that patients with early-stage breast cancer had decreased expression of genes involved in cell cycle and proliferation, pyrimidine metabolism, and p53 signaling pathways in response to everolimus.…”
Section: Rapalogs: Rapamycin Analogsmentioning
confidence: 99%